Impact of Diabetes Mellitus on Urinary Continence Recovery after Radical Prostatectomy: a Systematic Review and Meta-Analysis - Huang, Jianlin; Wang, Yu; An, Yu; Liao, Yong; Qiu, Mingxing (Urology Journal, 2020)
Purpose: To evaluate the impact of diabetes mellitus (DM) on the recovery of urinary continence (UC) after radical prostatectomy (RP). Materials and Methods: A systematic review of English articles was performed in August 2019, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Trials were identified in a literature search of PubMed, Embase, Cochrane Library and Web of Science using appropriate search terms. All comparative studies reporting diabetes mellitus, study characteristics, and outcome data including the relationship between diabetes mellitus and urinary continence data were included. Continence rates at different time after RP were compared. Odds ratio (OR) was used for the comparison and all the results were presented with 95% confidence intervals (CIs). Results: Seven cohort studies comprising with 5944 participants were included, the percentage of DM patients was 8.7%. The results showed that DM decreased urinary continence rates at 12 months after RP (OR 0.54, 95%CI 0.36 to 0.81, p = 0.003). The continence rates were not significantly different between DM and Non-DM groups at short-term (catheter removal, 3 months, 6 months) and long-term (>12 months). When stratified by the surgical approaches, the pooled results in patients who underwent robot -assisted radical prostatectomy (RARP) were similar to results of the overall analysis. Conclusion: DM has an adverse impact on the recovery of UC during the intermediate-term after RP. Well-designed trials with strict control of confounders are needed to make results more comparable.